2015
DOI: 10.1177/2325957415600700
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of a Pharmacist-Led Antiretroviral Stewardship Program on Reducing Drug Interactions in HIV-Infected Patients

Abstract: An ARVSP is critical in the prevention of CSDDIs and errors to improve safety in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
1
18
0
1
Order By: Relevance
“…A majority (91.7%) of the pharmacist interventions for the problems identified during the study were accepted by the physicians (23). Billedo et al showed that the clinical pharmacist's participation in the Antiretroviral Stewardship Program contributed to a reduction of drug-related errors and improvement of drug safety in patients (24). Evaluation of patients' treatments and recommendations to physicians and patients during ART by pharmacists have been reported by numerous studies in literature (10,22,25).…”
Section: Discussionmentioning
confidence: 92%
“…A majority (91.7%) of the pharmacist interventions for the problems identified during the study were accepted by the physicians (23). Billedo et al showed that the clinical pharmacist's participation in the Antiretroviral Stewardship Program contributed to a reduction of drug-related errors and improvement of drug safety in patients (24). Evaluation of patients' treatments and recommendations to physicians and patients during ART by pharmacists have been reported by numerous studies in literature (10,22,25).…”
Section: Discussionmentioning
confidence: 92%
“… 1 Pharmacist interventions in patients infected with HIV can contribute to the maintenance of antiretroviral therapy and improvement in clinical outcomes. 2 Partial adherence or non-adherence to ART is one of the main barriers to its effectiveness. 3 , 4 In this context, studies that identify the benefits of different pharmaceutical care practices in supporting adherence to antiretroviral therapy are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…l virus de la inmunodeficiencia humana (VIH), es uno de los principales problemas de salud pública y para el 2016 había aproximadamente 36,7 millones de personas infectadas 1 . La terapia anti-retroviral combinada (TARc) ha permitido un control en la progresión de la infección, ya que contribuye a la disminución de la morbi-mortalidad y al aumento de la esperanza de vida en los pacientes infectados 2, 3 .…”
unclassified